Indicators of Economic Activity: A Review - Sierra Suárez, Lya Paola; Collazos-Rodríguez, Jaime Andrés; Sanabria-Domínguez, Johana; Vidal-Alejandro, Pavel (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Economic indicators are used to measure the performance of the economy when other indicators, such as gross domestic product, may not provide information about the state of the economy in real time. This article provides a review of national and international literature about the construction of indicators of economic activity. Additionally, a summary of the methodology most commonly used in the construction of indices of economic activity, Factorial Dynamic Model (MFD) and different types of estimation is offered.